195 Nice 95 and non anginal chest pain: reassuring patients without investigation. (4th June 2021) - Fellows, Sarah; Kopanska, Agnieszka; Chandrasekaran, Badrinathan; Barnes, Edward
Abstract : Background: NICE 95 guidance (2016) tells us that patients presenting with stable non-anginal chest pain do not require further investigation where clinical suspicion of underlying coronary disease is deemed unlikely. This relies on the clinical acumen of the healthcare practitioner assessing patients with no pre-test probability score recommended in the current guidelines (a change from 2009 guidance). The European Society of Cardiology (ESC), however, recommend the use of a pre-test probability score to aid decision making in such cases. We believe that the current practice of reassuring this group of patients without investigation is safe and that a formalised pre-test probability score does not provide additional reassurance.Method:A retrospective single centre cohort study of all cases assessed in a face-to-face nurse led rapid access chest pain clinic (RACP) where patients were discharged without investigation. Pre-test probability scores were calculated according to the ESC chronic coronary syndromes guideline (2019) and major adverse cardiovascular events (MACE) reviewed with a mean follow up time of 3.8 years. Results: A total of 1221 cases were reviewed between March 2015 and November 2018. 73 patients were excluded where they were referred on for further cardiologist assessment (54) or where insufficient data was available (19). Of the remaining 1148, 44 patients (1% per year) went on to be diagnosed with coronary artery disease, 26 of which had no prior history of IHD. 25 patients presented as an emergency with acute coronary syndrome. We observed a total of 19 deaths (0.44% per year) that could have been attributable to cardiac disease however our follow up is limited to locally available data. 38 patients were re-referred for investigation of chest pain; 33 of which had normal investigations and 5 patients were reassured and discharged again without investigation. Only 43% of patients seen and discharged without investigation had a low risk pre-test probability score of <5% with 21% having a high pre-test probability score. Whilst the majority of adverse events were seen in those with intermediate and high pre-test probabilities, overall adverse event rate remained low over a long follow up period. Conclusion: Whilst a pre-test probability score may help to determine which patients are more likely to go onto develop coronary disease, the majority of patients discharged with non anginal pain were in the intermediate and high risk groups. We recognise that clinical suspicion of coronary disease is an important part of the decision making process and that this model relies on the clinical skill of the specialist nurses in RACP clinics. We have demonstrated that where chest pain is non-anginal in character, patients can be safely reassured and discharged without investigation with a low adverse event rate over a long follow up period, supporting the current NICE 95 guidance. Conflict of Interest: None